An Early Supported Discharge (ESD) Model of Care for Older Adults Admitted to Hospital: A Descriptive Cohort Study - Williams S; Whiston A; Morrissey AM; O'Riordan C; O'Connor M; Hartigan D; Devlin C; Galvin R (Clinical Interventions in Aging)
Susan Williams,1 Aoife Whiston,2 Ann-Marie Morrissey,1 Clíona O’Riordan,1 Margaret O’Connor,3 Deirdre Hartigan,1 Collette Devlin,1 Rose Galvin1 1School of Allied Health, Faculty of Education and Health Sciences, Ageing Research Centre, Health Research Institute, University of Limerick, Limerick, Ireland; 2Department of Psychology, Faculty of Education and Health Sciences, University of Limerick, Limerick, Ireland; 3Department of Ageing and Therapeutics, University Hospital Limerick, Dooradoyle, Limerick, IrelandCorrespondence: Susan Williams, School of Allied Health, Faculty of Education and Health Sciences, Ageing Research Centre, Health Research Institute, University of Limerick, Limerick, Ireland, Email Susan.Williams@ul.ieBackground: Early supported discharge (ESD) facilitates early discharge from acute hospitals with continued rehabilitation in the home environment from a multi-disciplinary team at the same intensity as would be received in the inpatient setting. Emerging evidence suggests it can have a positive impact on the care of older adults on discharge from the acute hospital setting to home. This study aims to characterize an inreach model of ESD for older adults discharged from four hospitals in the Mid-West of Ireland and describe its impact on clinical and process outcomes at 30 and 180 days.Methods: Consecutive older adults referred for ESD from four hospitals were recruited over six-months. Baseline assessments were carried out on initial review, and patients were followed up at 30 and 180 days by an independent outcome assessor. Outcomes measured include functional status, frailty, health related quality of life, mortality, and healthcare utilization.Results: One hundred and thirty older adults (mean age 76.62 years, SD 9.81 years) were recruited, 44 for surgical complaints and 86 for medical complaints. The ESD service was provided over a median of 31 (medical) - 44 (surgical) days, primarily by physiotherapy and occupational therapy. The incidence of functional decline was 16.41% at 30 days and 27.5% at 180 days. There was a significant improvement in the self-reported function from index visit 72.94 (19.50) mean standard deviation (SD) to 30 days 84.05 (21.08) mean (SD) which was maintained at 180 days 80.53 (30.93) mean (SD). Frailty was independently associated with incidence of functional decline at 30 days (OR 2.06, 95% CI 1.39 to 3.06) and 180 days (OR 1.7, 95% CI 1.29 to 2.24).Conclusion: An ESD model of care can have significant effects on patient outcomes for older adults admitted to hospital at 30 and 180 days, without increasing the risk of unscheduled Emergency Department re-presentation. Future research should explore the impact of an ESD model of care on specific older adult cohorts.Keywords: early supported discharge, older adult, hospitalization, patient discharge, cohort studies